Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The question is : Show that $$e^{{c\over 2}(z-{i \over z})}={\sum_{n=-\infty}^\infty} a_nz^n$$

The question solved using Laurent's Series expansion where

$$a_n={1\over 2\pi i}\int_cf(z){dz \over z^{n+1}}$$ and $$b_n={1\over 2\pi i}\int_cf(z){dz \over z^{1-n}}$$

Then integrating and solving for $a_n$ i get

$$a_n={1\over 2\pi}\int_0^{2\pi}\cos(n\theta-c\sin\theta)d\theta$$

Now, we see that the function remains unaltered if $z$ is replaced by $-1\over z$

So far so good, now I don't understand the steps after this, it is given that :

so, $b_n=(-1)^na_n$ , It follows that

$$e^{{c\over 2}(z-{i \over z})}={\sum_{n=0}^\infty a_nz^n} + {\sum_{n=1}^\infty b_nz^{-n}} = {\sum_{n=-\infty}^\infty a_nz^n}.$$

Basically I don't understand how $b_n=(-1)^na_n$ and also the last part where the summation has been extended to $-\infty$

share|cite|improve this question
Since $f(z)=f(-1/z)$, the coefficient of $z^n$ is the same as the coefficient of $(-1/z)^n$, which is $(-1)^n z^{-n}$. – 40 votes Jul 19 '13 at 1:51

For the second part, I will start from $b_n = (-1)^n a_n$. Then $\sum^{+\infty}_{n=-\infty} a_n z^n = (\sum^{-1}_{n=-\infty} + \sum^{+\infty}_{n=0}) a_n z^n $. In the first sum here, transform the (dummy) summation index to $m=-n$, then this sum becomes $\sum^{+1}_{m=+\infty} a_{-m} z^{-m}$. If you now look at the integral expressions for $a_n$ and $b_n$ you gave, you see that $a_{-n}$ equals $b_n$. Hence substituting in the first sum gives $\sum^1_{+\infty} b_m z^{-m}$, which is the same as $\sum^{+\infty}_{1} b_m z^{-m}$, i.e., the second sum in your expression.

share|cite|improve this answer

IMHO, there could a typo in the power of $(-1)$ for the expression for $b_n$. This is what I got: substitute $y=-1/z$ in the integral for $a_n$, this gives $a_n = \int_c f(-1/y) (-y)^{n+1} y^{-2} dy = (-1)^{n-1} \int_c f(-1/y) (1/y)^{1-n} dy = (-1)^{n-1} \int_c f(y) (1/y)^{1-n} dy = (-1)^{n-1} b_n$.

Therefore, $b_n = (-1)^{n-1} a_n$.

Maybe I made a sign error somewhere, in which case $b_n = (-1)^{n} a_n$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.